Successful treatment of childhood-onset Cushing's disease is associated with persistent reduction in growth hormone secretion. - Carroll, P; Monson, J; Grossman, AB; Besser, G; Plowman, P; Afshar, F; Savage, M (2004)
OBJECTIVE: Although Cushing's disease (CD) rarely occurs in childhood, affected children commonly fail to achieve predicted adult height. Hypercortisolaemia results in reduced GH secretion and GH-deficiency may persist or demonstrate delayed recovery after successful treatment of CD in adults. Whether recovery of spontaneous GH secretion occurs following treatment of childhood CD has yet to be established. DESIGN AND PATIENTS: We performed a retrospective analysis of the GH status of 13 children (10 males; 12.8 +/- 1.0 years, mean +/- SE) who had undergone successful treatment of CD that occurred prior to the completion of linear growth. Each underwent transsphenoidal hypophysectomy, resulting in satisfactory control of glucocorticoid levels in 7/13 (54%). The remaining six patients (46%) received fractionated external beam irradiation (4500 Gy). At the time of GH assessment, circadian dynamics of cortisol were normal in eight patients and five were receiving titrated glucocorticoid replacement. MEASUREMENTS: GH status was assessed using the peak response to a provocative stimulus. Eleven out of 13 underwent testing with insulin-induced hypoglycaemia (nadir plasma glucose <!--= 2.2 mmol/l) and glucagon provocation was used in 2/13. Severe GH-deficiency was defined as a peak GH response < 9 mU/l, and a normal response as --> 30 mU/l. Intermediate values were taken to represent subnormal GH status. Assessment of GH status was performed 39 +/- 10 months (median +/- SE) following successful treatment (range 9-108 months). RESULTS: Using these criteria 4/13 (31%) patients had severe GH-deficiency. Only 2/13 (15%) had a normal response. 7/13 (54%) achieved peak GH levels in the subnormal range. Those with multiple pituitary hormone deficiencies were most likely to have lower peak GH levels, but there was no clear effect of pituitary irradiation or relationship between duration post cure and peak GH response. CONCLUSION: GH-deficiency is common and may persist for many years following successful treatment of CD prior to completion of linear growth. External radiotherapy does not necessarily result in severe GH-deficiency in the short term. Assessment of GH status and consideration of GH treatment should be considered following treatment of CD in childhood and adolescence in order to maximize the opportunities to achieve a satisfactory final adult height. In those with subnormal GH responses, continued assessment is necessary to determine whether the GH axis subsequently recovers or if these patients develop features of the adult GH-deficiency syndrome.